INDIKASI MORAL HAZARD PADA PEMBIAYAAN MUDHARABAH DAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA - Siti Aisiyah Suciningtias (Jurnal Dinamika Ekonomi & Bisnis, 2017)
This study aims to analyze the presence of Moral Hazard indications on Mudaraba and Murabaha Financing at Islamic Banks in Indonesia. It uses the NPF variable to measure the moral hazard indication. If the NPF is high, then there will be indications of moral hazard; but if the value of the NPF is low, then there will be no indication of moral hazard on Islamic banking. The population in this research is the Islamic banking in Indonesia in the period of 2007 to 2012. The sampling method is purposive sampling technique with the following criteria: First, Islamic banks which are enrolled in Legal Islamic Banks database; Second, Islamic banks which publish their Quarter financial statements during the period of 2007 – 2012; Third, Islamic Banks that have complete variable database to be studied. The data taken is the data that produces a positive return value. So, the numbers of sample that pass several measurements are defined. It is found 3 Islamic banks used as sample: BMI, BMSI, and BSM. The analyses used in this study are multiple linear regressions and using the SPSS software. The independent variables of the study are the growth of GDP, the return ratio of Mudaraba financing compared with the return of total financing (RR) and the Return Ratio of murabaha receivables allocation compared with the Return of Total Financing (RF).The findings show that the GDP (X1) has a negative and significant influence. This negative influence shows that there is no indication of moral hazard in Islamic banks in terms of macroeconomic. Meanwhile, RR (X2) has a positive and significant influence toward the NPF. It means that there is indication of moral hazard in Islamic banks related to mudaraba financing. However, RF (X3) has a positive but not significant influence toward the NPF. It means that the RF variable has no influence on the NPF. So that, the RF variable cannot prove that there is an indication of moral hazard in Islamic banking. Generally, it can be concluded that Islamic banking in Indonesia tends to choose a smaller risk in murabaha financing. In murabaha financing, the risk of moral hazard is lower than in mudharabah financing. Banks tend to be more focus on murabaha financing so as to better carry out maintenance of the debtor.